Light-emitting agents for noninvasive assessment of kidney function - Huang, Jiaguo; Gretz, Norbert (ChemistryOpen, 2017)
The noninvasive assessment of kidney function and diagnosis of kidney disease have long been challenges. Traditional methods are not routinely available, because the existing protocols are cumbersome, time consuming, and invasive. In the past few years, significant progress in the area of diagnosing kidney function and disease on the basis of light-emitting agents has been made. Herein, we briefly review light-emitting agents, including organic fluorescent agents and inorganic renal clearable luminescent nanoparticles for the noninvasive and real-time monitoring of kidney function and disease. Moreover, some significant requirements and strategies regarding the design of ideal glomerular filtration rate agents and renal clearable nanoparticles are discussed. Finally, we discuss future challenges in expediting clinical translation of these developed light-emitting agents, along with considerations of the efforts that need to be made to develop new agents and diagnosing kidney disease.